The Other Austrians - Tamara Ehs (Journal on European History of Law)
Some observers of the recent economic crisis compare it to the Great Depression of the 1930s and discuss interwar ideas bearing on these questions such as those of “the Austrians”. There is a lively treatment of Ludwig Mises and his pupils but the other Austrian discourse of this time is neglected, that of the three full professors of political economy at the law faculty of the University of Vienna: Othmar Spann, Hans Mayer and Ferdinand Degenfeld-Schonburg – “the Other Austrians”. This paper calls them to mind and gives an insight into their stances on the economic crisis.